Usefulness of STOPPSTART criteria to assess appropriateness of medicines prescribed to older adults in a resource-limited setting - Siripala, U. G. S.; Premadasa, S. P. K.; Samaranayake, N. R.; Wanigatunge, C. A. (Springer, 2019)
Attached
Keywords: Medicines appropriateness • Older adults • Resource-limited settings • Sri Lanka • STOPP/START criteria